Comparison of sustainable biosorbents and ion-exchange resins to remove Sr2+ from simulant nuclear wastewater: Batch, dynamic and mechanism studies - Rae, Ian B.; Pap, Sabolc; Svobodova, Dagmar; Gibb, Stuart W. (The Science of the total environment, 2019)
Removal of Sr2+ from aqueous media presents particular challenges, especially in complex wastes such as nuclear industry liquors. Commercial sorbents while effective, can be highly expensive and subject to negative effects from competing ions. Here we evaluate two potential biosorbents (crab carapace and spent distillery grain) as potential alternatives and compare their performance to two commercial sorbents for Sr2+ removal at industrially relevant concentrations (low mg/L). Physical and structural characterization of the materials was undertaken, and batch and dynamic studies were performed on Sr2+ solutions and simulated nuclear wastewater. Sorption performance was quantified with respect to contact time, initial concentration and ion-competition. Removal efficiencies were 20–70% for the biosorbents compared to 55–95% for the commercial materials. Results indicated sorption was predominantly through monolayer coverage on homogenous sites and could be described using a pseudo-second-order kinetic model. Studies with the simulant liquor showed Sr2+ sorption was reduced by 10–40% due to ion-competition for sites. Characterization of biosorbents before and after Sr2+ sorption suggested that outer-sphere complexation and ion-exchange were the primary Sr2+ removal mechanisms. The efficiency of crab carapace for Sr2+ removal from aqueous media (with adsorption capacity 3.92 mg/g.) at industrially relevant concentrations, together with its mechanical stability, implementation and disposal cost, makes it a competitive option compared to other biosorbents and commercial materials reported in the literature. [Display omitted] •Valorisation of food and drink processing residues in water decontamination•A novel, low-cost approach in sorption for effective Sr2+ removal•Sorption occurs through outer-sphere complexation and ion-exchange mechanisms.•Ion-competition with Na+, K+ and Ca2+ suppressed Sr2+ removal in simulant waste liquor.•Crab carapace has potential as a low-cost sorbent for Sr2+ removal at trace concentrations.